2018
DOI: 10.1093/ajcp/aqy049
|View full text |Cite
|
Sign up to set email alerts
|

Survey-Defined and Interview-Elicited Challenges That Faced Ethiopian Government Hospital Laboratories as They Applied ISO 15189 Accreditation Standards in Resource-Constrained Settings in 2017

Abstract: The survey and interviews specified nine major challenges for Ethiopian government hospital laboratories that seriously obstruct meeting ISO 15189 demands.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(25 citation statements)
references
References 16 publications
1
23
0
Order By: Relevance
“…The most important aspect of pursuing accreditation is good teamwork and to encourage laboratory personnel on possibilities to enhance the work done. 49 The communication system put in place for improvement plans and related goals must include all laboratory personnel. This can be implemented by having frequent staff meetings and sharing meeting minutes with those who did not attend the meetings.…”
Section: Effective Continual Improvementmentioning
confidence: 99%
See 4 more Smart Citations
“…The most important aspect of pursuing accreditation is good teamwork and to encourage laboratory personnel on possibilities to enhance the work done. 49 The communication system put in place for improvement plans and related goals must include all laboratory personnel. This can be implemented by having frequent staff meetings and sharing meeting minutes with those who did not attend the meetings.…”
Section: Effective Continual Improvementmentioning
confidence: 99%
“…However, most sub-Saharan African public sector laboratories, to varying extents, have failed the accreditation process. 49 The survey-defined and interviewelicited challenges that faced Ethiopian government laboratories as they apply IS0 15189 showed that all laboratory heads agreed that poor-quality equipment had obstructed the accreditation process. 49 Loss of accreditation occurs in many ways; either voluntarily, imposed by the accreditation body or partial suspension whereby only part of the scope of accreditation is suspended voluntarily or by the accreditation body.…”
Section: Loss Of Accreditationmentioning
confidence: 99%
See 3 more Smart Citations